Determinants of change in blood pressure in Ghana: Longitudinal data from WHO-SAGE Waves 1-3. - Elias K Menyanu; Barbara Corso; Nadia Minicuci; Ilaria Rocco; Joanna C Russell; Lisa J Ware; Glory Chidumwa; Nirmala N Naidoo; Richard B Biritwum; Paul R Kowal; Aletta E Schutte; Karen E Charlton (PLoS ONE)
The prevalence of hypertension is increasing in low- and middle-income countries, however statistics are generally derived from cross sectional surveys that utilize different methodologies and population samples. We investigated blood pressure (BP) changes over 11-12 years in a large cohort of adults aged 50 years and older (n = 820) included in the World Health Organization's Study on global AGEing and adult health (WHO-SAGE Ghana) Wave 1 (2007/8) with follow up in Wave 3 (2019). Participants' BP were measured in triplicate and a survey completed at both time points. Survey instruments collected information on sociodemographic characteristics, lifestyle, health behaviors and chronic conditions. While no significant difference was found in systolic BP between Waves 1 and 3, diastolic BP decreased by 9.7mmHg (mean = 88.6, 15.4 to 78.9, 13.6 respectively) and pulse pressure increased by 9.5mmHg (44.8, 13.7 to 54.3, 14.1). Awareness of hypertension increased by 37%, from (20% to 57%), but no differences were found for the proportion of hypertensives receiving treatment nor those that had controlled BP. Mixed effects modelling showed a decrease in diastolic BP was associated with increasing age, living in rural areas and having health insurance. Factors associated with an increased awareness of hypertension were residing in urban areas, having health insurance and increasing body mass index. While diagnosis of hypertension has improved over time in Ghana, there is an ongoing need to improve its treatment in older adults.